PETROCHEMISTRY OF ORDINARY CHONDRITES AND A MODEL FOR THE GENESIS OF PLANETS AND THEIR SATELLITES - Marakushev A.A.; Chaplygin O.V. (My University, 2002)
Systematic regularities in the variations of parameters of ordinary chondrites relating them to iron meteorites like Netschaevo are deduced from a review of the chemical and oxygen isotopic compositions of ordinary chondrites. Iron meteorites of this type, which were genetically related (in their molten state) to ordinary chondrites, gave rise to the evolution of chondritic systems in the form of the heavy cores of parent fluid protoplanets in the succession HH-H-L-LL. The evolution of chondritic magmatism along this succession is thought to have been caused by hydrogen loss by the planets under the effect of the Sun and ended with the completion of the surface degassing of the planets. Terrestrial planets situated not far from the Sun were the first to undergo degassing, and, correspondingly, their chondritic material was more primitive (consisted of iron meteorites and HH chondrites) than that of the asteroid belt, which contains the full chondritic succession (HL-LL). The conclusion that iron cores are possessed by the most primitive chondritic planets receives further support from experimental evidence on modeling of the genesis of HH chondrites. A generalization of petrochemical data is used as the basis for a chondritic model for the origin of iron-stony planets and an achondritic model for the satellites of the giant planets. The models make use of information on the oxygen isotopic composition of chondrites and achondrites, as well as lunar and terrestrial rocks. Understanding of the fact that iron-stony planets and satellites were produced by protoplanets, such as Jupiter, provides insight into the nature of their endogenic activity, which resulted in the rejuvenation of the planetary crusts. The general trends of these processes in the planets was determined by both internal and external factors (gravitational effect of the Sun and near-Sun planets). The Sun's gravitational influence on Mercury resulted in two oppositely directed trends in the maximum volcanic activity, one of which gave rise to the giant, 1300 km in diameter, Caloris Basin (Planitia Caloris). This is explained by Mercury's resonant, although asynchronous, revolution around the Sun and, consequently, the fact that, when at perihelion, i.e., when the Sun's gravitational effect is at a maximum, the near-solar position is always occupied by either Caloris itself or its antipodal terrane of volcanic depressions at Mercury's opposite side. The gravitational effect of parent planets on the endogenic evolution of their satellites is more stable and unambiguous thanks to the resonant and synchronous revolution of the satellites. The sides of satellites constantly facing the parent planets are characterized by a higher endogenic activity than those in the opposite sides. This also pertains to their primary layering and the processes of their crustal rejuvenation. The eucritic crust in the Moon's far side is much thicker (80 km) than in its near side (60 km), where all endogenic processes of its rejuvenation are focused and resulted in lunar maria. Within the latter, the crustal thickness further decreased, as is reflected in mascons. Similar crustal renewal on Venus and Mars are much more advanced, as follows from the occurrence of larger maria at these planets. On Mars, mare structures with a thinner crust are combined within a vast continuous mare area, which nearly fully covers the planet's northern hemisphere. This also holds for the Earth, whose primary continental marine and oceanic crust types (which are typical of other terrestrial planets) have been fully obliterated by the folded continental and the oceani